1992
DOI: 10.1111/j.1651-2227.1992.tb12284.x
|View full text |Cite
|
Sign up to set email alerts
|

Human gastric lipase: ontogeny and variations in children

Abstract: The aim of this study was to investigate the precise origin of the acid pre‐duodenal lipase during human development and to evaluate its possible changes, at the tissue level, in children with gastritis or pancreatic insufficiency. Human gastric lipase appears around the 11 th week of gestation and increases slowly during pre‐ and postnatal development. It is localized in the fundus of the stomach without any lingual localization. Human gastric lipase reaches its adult level in the third month of life, and doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…reported that in seven children with gastritis, the activity of HGL was normal, while in the two remaining children, only a trace HGL activity was found. They concluded that the activity of HGL is only rarely reduced in patients with gastritis [13]. In our study, the age of the patients was in a similar range (adolescents), and all of them had gastritis.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…reported that in seven children with gastritis, the activity of HGL was normal, while in the two remaining children, only a trace HGL activity was found. They concluded that the activity of HGL is only rarely reduced in patients with gastritis [13]. In our study, the age of the patients was in a similar range (adolescents), and all of them had gastritis.…”
Section: Discussionsupporting
confidence: 61%
“…in 1992 [13]. The authors studied a group of 55 children aged from zero to 17 years, including only nine patients with gastritis.…”
Section: Discussionmentioning
confidence: 99%
“…The low pH is known to favor the release of Ca 2ϩ (16)(17)(18), and casein is precipitated. The acid lipase hydrolyses triglycerides, and fatty acids are released (25,26). By chance, we happened to purify the apoptosisinducing form of ␣-lactalbumin from human milk after precipitation of casein at low pH, thus mimicking the conditions in the stomach of the breast-fed child (7,27).…”
Section: Discussionmentioning
confidence: 99%
“…HGL is not only the first lipase found along the gastro-intestinal tract, it is also produced at high levels in the early life while the production of pancreatic enzymes and bile is still limited [12][13][14]. In the neonatal context, lipid digestion is crucial for cerebral and global development and growth, and HGL appears as a central enzyme in this process [12,14].…”
Section: Introductionmentioning
confidence: 99%
“…In the neonatal context, lipid digestion is crucial for cerebral and global development and growth, and HGL appears as a central enzyme in this process [12,14]. HGL is able to initiate the lipolysis of milk fat globules, what is not readily done by pancreatic lipase [15].…”
Section: Introductionmentioning
confidence: 99%